Mediating and Marketing Factors Influence the Prescription Behavior of Physicians: An Empirical Investigation - Rizwan Raheem Ahmed; Jolita Vveinhardt; Dalia Streimikiene; Muhammad Awais (Amfiteatru Economic Journal, 2016)
The authors present general review of the literature and the results of an empirical research on the subject. A cross-sectional questionnaire-based survey was conducted, being answered by 350 respondents: mix of graduate and post graduate doctors of private and public hospitals of Karachi City, and pharmaceutical personnel (mix of sales and marketing) of national and multinational pharmaceutical companies operating in Pakistan. To test hypothesis, structural equation modelling (SEM) was employed using AMOS 7 software package. As data are normally distributed, maximum likelihood method of estimation was used. Factorial ANOVA also enables us to examine the interaction effect between the factors. The results from factorial ANOVA test all the hypotheses of model, and results were declared significant at p <0.05. Findings are interesting as they establish association between variables (scientific literatures, promotional material, regular follow up, CMEs & conferences, personalized activities) and prescription behavior of doctors mediated by strong phenomenon of medical representative PR and brand image of a company/product in changing the prescription behavior of doctors. Based on the results of this study, the pharmaceutical companies can device better marketing strategies keeping in view of these mediating effects. The article presents only two mediating and five marketing factors, whereas, more marketing and mediating variables can be added and tested, so, in future this gape can be overcome by other researchers. Moreover, a larger sample size could be applied and the scope of study can be enhanced.
Keywords: M30; M31; M39; 330; prescription behaviour; mediating factors; marketing variables